Lattice design and experimental studies of nonlinear resonance at the Cornell Electron Storage Ring - S. T. Wang; V. Khachatryan; P. Nishikawa (Physical Review Accelerators and Beams, 2023)
The predominant source of nonlinearity in most existing accelerators are sextupoles, which introduce nonlinear resonances. When the horizontal tune of an accelerator is near such a resonance line (nν_{x}), stable fixed points (SFPs) may appear in the horizontal phase space to form a second closed orbit different from the “zero” closed orbit. The stable islands in phase space surrounding the SFPs are also referred as transverse resonance island “buckets” (TRIBs). However, the TRIBs are not always present near a resonance line in a storage ring. Necessary conditions for TRIBs formation will be discussed in this paper. A 6-GeV lattice with the horizontal tune near a third-order resonance at 3ν_{x}=50 is then designed for the Cornell Electron Storage Ring (CESR). After loading this lattice into CESR, the TRIBs are observed while adjusting the horizontal tune near the third-order resonance, consistent with particle tracking simulations. TRIBs rotation in the horizontal phase space are also experimentally demonstrated with adjustment of a sextupole knob. These results are in good agreement with the theoretical calculation.